Trends and Determinants of Female Labor Force Participation in Morocco : An Initial Exploratory Analysis - Lopez-Acevedo, Gladys; Devoto, Florencia; Morales, Matías; Roche Rodriguez, Jaime (World Bank, Washington, DC, 2021)
The U-shape theory argues that at early stages of development, countries experience a reduction in the female labor force participation, eventually followed by a recovery. In Morocco, female labor force participation is now lower than it was two decades ago due to several factors that are discussed in the paper. There is also a persistent 50-percentage-points gender gap in labor force participation rates, despite improvements typically related to development and female inclusion—such as a higher gross domestic product per capita, lower fertility rates, and better access to education. At the same time, urban job creation has not been able to offset rural job destruction nor the increase in the working age population for both genders. Using data from the Moroccan Labor Force Survey, the World Values Survey, and the Arab Barometer, probit models and a multinomial logit are estimated to explore the challenges affecting female insertion into the labor market. The findings show that higher educational attainment increases the probability of female participation, but this relationship has decreased over time, not being enough to offset other obstacles caused by other individual and household characteristics. Being married and the presence of other inactive women are found to decrease female participation. The educational level of the head of household (typically men) increases female inactivity, suggesting that potentially gender roles may drive women out of the labor market and slow the recovery in women’s participation.